Optimization of Papaya Leaf Extract Cream Using Stearic Acid and Triethanolamine via Simplex Lattice Design - Siwi, Andini Prabandaru; Priyanto, Widodo; Novita, Mega; Marlina, Dian (Fakultas Farmasi, Universitas Surabaya, 2025)
Papaya leaves (Carica papaya L.) are known to contain bioactive compounds such as flavonoids, alkaloids, tannins, and saponins, which exhibit antiseptic, anti-inflammatory, antifungal, and antibacterial properties, making them promising for topical pharmaceutical preparations. However, achieving optimal physical characteristics in cream formulations requires careful selection and proportioning of emulsifiers. This study investigates the effect of varying ratios of stearic acid and triethanolamine on the physical properties of creams containing ethanol-extracted papaya leaf extract. The extract was obtained via maceration using 96% ethanol and confirmed to contain active compounds through phytochemical screening and thin-layer chromatography. Eight formulations were developed using a Simplex Lattice Design (SLD) with stearic acid concentrations ranging from 15–17% and triethanolamine from 2–4%. Physical evaluations included tests for pH, viscosity, adhesion, and spreadability. All formulations met standard of cream quality requirements, but the optimal formula was identified at 15.20% stearic acid and 3.79% triethanolamine, offering the most desirable physical characteristics. This formulation strategy demonstrates the potential for producing effective and stable papaya leaf creams, with implications for natural-based dermatological product development. Submitted: 05-05-2025, Revised: 18-06-2025, Accepted: 25-06-2025, Published regularly: June 2025